2020
DOI: 10.1183/23120541.00458-2020
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and time-course of excess mortality during COVID-19 outbreak: population-based empirical evidence from highly impacted provinces in northern Italy

Abstract: BackgroundThe real impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on overall mortality remains uncertain as surveillance reports have attributed a limited number of deaths to novel coronavirus disease 2019 (COVID-19) during the outbreak. The aim of this study was to assess the excess mortality during the COVID-19 outbreak in highly impacted areas of northern Italy.MethodsWe analysed data on deaths that occurred in the first 4 months of 2020 provided by the health protection agencies (HP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
(21 reference statements)
1
22
0
Order By: Relevance
“…Italy has rapidly become one among the countries most affected by the novel coronavirus disease 2019 (COVID-19) pandemic, after the detection of the first confirmed case in late February 2020 [ 1 , 2 ]. As for other countries, the rapid spread of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) has posed an unprecedented challenge, with a high number of confirmed cases—reaching more than 2.8 million cases and almost 97,000 deaths by February 25, 2021, an enormous death toll and impactful consequences on the entire healthcare service system [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Italy has rapidly become one among the countries most affected by the novel coronavirus disease 2019 (COVID-19) pandemic, after the detection of the first confirmed case in late February 2020 [ 1 , 2 ]. As for other countries, the rapid spread of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) has posed an unprecedented challenge, with a high number of confirmed cases—reaching more than 2.8 million cases and almost 97,000 deaths by February 25, 2021, an enormous death toll and impactful consequences on the entire healthcare service system [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with the goal to fill this gap, the presented study aimed to primarily estimate the prevalence and time-persistence of SARS-CoV-2 antibodies, and to suggest factors associated with positivity among different categories of workers from a densely populated vast geographical area of northern Italy, which was hit hardest in terms of cases and deaths during the first epidemic wave (March—May 2020) [ 5 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus on the sex difference in the excess mortality during the COVID-19 outbreak. Two studies reported higher excess deaths in male than in females [ 11 , 31 ], while inconclusive sex difference was reported in several locations [ 17 , 20 ]. Similarly, we did not identify a significant sex difference.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, examining the excess mortality by sociodemographic status could reveal the inequalities in the effects of COVID-19 outbreak and further illuminate targeted approaches to reducing the adverse effects of the outbreak. Age and gender disparities have been explored previously [ 6 – 9 , 11 – 13 , 17 20 ]. To our knowledge, there is no previous study estimating the excess deaths for subpopulations of other sociodemographic status, such as marital status and occupation class.…”
Section: Introductionmentioning
confidence: 99%
“…The growing body of evidence on COVID-19 has led to a development of numerous management guidelines and new treatment options [ 9 11 ]; however, the impact of the pandemic inevitably extends beyond the patients infected with SARS-CoV‑2. Not only has an excess mortality been observed in several European countries during the first wave of the COVID-19 pandemic, but the number of excess deaths also surpassed the number of deaths attributed to COVID-19 in some countries [ 12 14 ]. Furthermore, the reduction of elective activity was accompanied by a decline in hospital admission rates for cardiovascular emergencies and an increase in intrahospital mortality [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%